Cordial intelligence - Villar Ezcurra, Alicia; Serrano Villar, María (Razón y fe, 2024)
The article addresses the characteristics of cordial intelligence, focusing on the importance of knowledge of the heart and the feeling of compassion from a moral point of view. After an introduction that refers to emotional intelligence and its psychological approach, the philosophical-moral perspective of cordial intelligence and the main meanings of the term “heart” are addressed. The background of the concept in the modernity of Blaise de Blaise Pascal and Jean-Jacques Rousseau is analyzed and the article ends with Adela Cortina’s references to cordial justice and Leonardo Boff’s references to the rights of the heart.
Keywords: cordial intelligence; heart; compassion; Pascal; Rousseau; A. Cortina; L. Boff